Cervical penetrating trauma: literature review - Freire, Artur Dantas; Lemos, Thiago Emanuel Véras; Oliveira-Júnior, Senival Alves de; Silva, Rielly de Sousa e; Rêgo, Amália Cinthia Meneses; Araújo-Filho, Irami; Medeiros, Aldo da Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2014)
Penetrating neck injuries are a major cause of morbidity and mortality in emergency admissions and surgical emergency services, so it is extremely important the anatomical and functional knowledge of the main structures affected during trauma. This article is a literature review of the major anatomical divisions, besides directing the physician to the diagnosis and best choice through selective management that seeks to identify patients who could benefit from surgical treatment of their wounds in an attempt to decrease the number of operations unnecessary.